1992
DOI: 10.1055/s-2008-1063472
|View full text |Cite
|
Sign up to set email alerts
|

Nissen Fundoplication for Gastro-Esophageal Reflux in Repaired Tracheo-Esophageal Fistula

Abstract: One hundred and fifty three patients had repair of tracheo-oesophageal fistula in a 15 year period of observation. Of these 55 had associated gastro-oesophageal reflux and of these 12 (8%) underwent a Nissen fundoplication. All patients manifested significant failure to thrive but weight-gain was documented in all patients following their fundoplication. Twenty five percent of patients demonstrated recurrent reflux in this study and emphasises the difficulty of treating gastro-oesophageal reflux in repaired tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…The recurrence rate following redo Nissen fundoplication in our series is higher for NI children (48%). Different studies have documented that the results of the first fundoplication are negatively influenced by the presence of neurological impairment and associated anomalies, both in children [6,8,[20][21][22][23][24], and infants [25] and several authors [24][25][26][27][28][29][30] have reported that the fundoplication is associated with a higher recurrence rate in patient with repaired oesophageal atresia (up to 24%). Associated anomalies were present in about 50% of the patients that required redo fundoplication.…”
Section: Discussionmentioning
confidence: 99%
“…The recurrence rate following redo Nissen fundoplication in our series is higher for NI children (48%). Different studies have documented that the results of the first fundoplication are negatively influenced by the presence of neurological impairment and associated anomalies, both in children [6,8,[20][21][22][23][24], and infants [25] and several authors [24][25][26][27][28][29][30] have reported that the fundoplication is associated with a higher recurrence rate in patient with repaired oesophageal atresia (up to 24%). Associated anomalies were present in about 50% of the patients that required redo fundoplication.…”
Section: Discussionmentioning
confidence: 99%
“…GER development has been speculated to he due to tension on the distal esophagus as a result of the anastomosis, which reduces the acuity of the angle of His. As division of the TEF and end-to-end esophageal anastomosis is considered to be the ideal method for neonates with EA-TEF, GER is expected to develop in 20-30% of such patients7, 10,14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, in most EA patients who have undergone anti-reflux surgery the symptoms are initially alleviated (17, 32, 33). Unfortunately, the positive effect of fundoplication is transient in a significant proportion of patients.…”
Section: Outcomes Of Fundoplication In Eamentioning
confidence: 99%
“…The wrap failure rates range between 20 and 45% (17, 3235). This is significantly higher rate than in those who undergo fundoplication without any underlying anatomic defect (33).…”
Section: Outcomes Of Fundoplication In Eamentioning
confidence: 99%